THE RELATIONSHIP BETWEEN JOB SATISFACTION AND ORGANIZATIONAL COMMITMENT AMONG PUBLIC SECONDARY SCHOOL TEACHERS - Bernadette Sanga, Jeffery Segal (Universiti Malaysia Sarawak (UNIMAS), 2021)
This study aims to identify the relationship between job satisfaction and components of organizational commitment among public secondary schools in Sri Aman, Sarawak. Therefore this study could make important contribution to extant research in management and organizational behavior. In the beginning of this study, the purpose, research question, and the need for the study is given. Then, literature is discussed about organizational commitment and job satisfaction that focusing on the relationship between them. The study produced 60 respondents who responded to the Google form link. The result showed that continuance was not found to have significant positive relationship with job satisfaction while affective, and normative commitment vice versa.